Deaf Students Higher Education System Using E-Learning - N. Vinoth; K. Nirmala (Journal of Education and Learning (EduLearn), 2017)
E-learning includes computer and electronically supported learning and teaching methods. E-learning used in Web-based learning, computer-based learning, virtual based learning and digital technology. It is a computer and network-enabled transfer of knowledge. it is the combination of learning and knowledge management.  It is also a useful tool that has contributed in facilitating education for deaf people. Deaf people are able to get benefit from this technology by increasing their knowledge and improving their skills. They can utilize the mobility feature to learn anywhere and at any time. E- Learn is an important one in higher education. Most of the students easily learn and develop skill and knowledge in e-learning method. Now a day’s e-learning tools are mostly used in learning method. In this paper we study about how deaf students used e-learning system in higher education institutions in and around  Chennai.